Pengaruh Financial Literacy dan Penggunaan Digital Payment Terhadap Perilaku Konsumtif Pada Mahasiswa Universitas Negeri Surabaya - Norida Canda Sakti; Caroline, Debby (Universitas Pahlawan Tuanku Tambusai, 2024)
This study is to examine how students at Universitas Negeri Surabaya's Economics Education Study Program use digital payments and their financial literacy in relation to their consumption behavior. This study employed a quantitative research technique. 141 students from four study programs S1 Pendidikan Ekonomi 2019, S1 Pendidikan Akuntansi 2019, S1 Pendidikan Tata Niaga 2019, and S1 Pendidikan Administrasi Perkantoran 2019 made up the research's sample. This study used multiple linear regression analysis, which was done with IBM SPSS software version 27, to ascertain the impact of financial literacy and the usage of digital payments on consumptive behavior. Based on the study's findings, it can be said that: (1) student consumption behavior is influenced by financial literacy; (2) student consumption behavior is influenced by digital payment; and (3) student consumption behavior is influenced by both financial literacy and digital payment together.